Diagnóstico de la práctica docente asociada al desarrollo socioeducativo de los estudiantes de Educación General Básica Media de la Unidad Educativa Cicalpa, cantón Colta, durante el año lectivo 2022-2023 - Ibujés López, María Daniela (2023)
The main objective of this research was to diagnose teaching practice associated with socio-educational development of the students of General Basic Middle Education of the Cicalpa Educational Unit of the Colta Canton. The specific objectives consisted of examining the teaching practice, identifying the socio-educational problems of the students and establishing a relationship between these variables. The methodology with which it was worked corresponds to a mixed approach with a field and descriptive research, considering as a population the tutors and students of Basic Media, to whom an interview and a survey were applied respectively. In this way, through the analysis of the data collected, it was evidenced that there are risk factors for the socio-educational development of students such as: lack of development of soft skills, thoughts of dropping out of school, work at home and lack of tutoring or reinforcement by teachers. All this, due to poor practice on the part of teachers to identify, prevent and address such problems.